Geminivirus–Host Interactions: Action and Reaction in Receptor-Mediated Antiviral Immunity - Marco Aurélio Ferreira; Ruan M. Teixeira; Elizabeth P. B. Fontes (Viruses, 2021)
In plant−virus interactions, the plant immune system and virulence strategies are under constant pressure for dominance, and the balance of these opposing selection pressures can result in disease or resistance. The naturally evolving plant antiviral immune defense consists of a multilayered perception system represented by pattern recognition receptors (PRR) and resistance (R) proteins similarly to the nonviral pathogen innate defenses. Another layer of antiviral immunity, signaling via a cell surface receptor-like kinase to inhibit host and viral mRNA translation, has been identified as a virulence target of the geminivirus nuclear shuttle protein. The Geminiviridae family comprises broad-host range viruses that cause devastating plant diseases in a large variety of relevant crops and vegetables and hence have evolved a repertoire of immune-suppressing functions. In this review, we discuss the primary layers of the receptor-mediated antiviral immune system, focusing on the mechanisms developed by geminiviruses to overcome plant immunity.